Peningkatan Sistem Inaportnet dan Kualitas Pelayanan Kapal Terhadap Kinerja pada Kantor Otoritas Pelabuhan Utama Tanjung Priok Jakarta - Agung Kwartama; Titis Ari Bowo; Lie Adek; Roma Dormawaty (Ocean Engineering : Jurnal Ilmu Teknik dan Teknologi Maritim, 2024)
The main Tanjung Priok Port Authority (OP) is the technical implementing unit as well as the highest coordinator at the port, having an important role in accelerating activities at the port. The Port Authority is within the Ministry of Transportation and is responsible to the Director General of Sea Transportation. The functions of the Port Authority include regulating, controlling and supervising port activities. To be able to integrate system services at ports, the Ministry of Transportation applies a system, namely the Inaportnet system. Inaportnet is an internet-based electronic service system to integrate standard port information systems in physically serving ships from all agencies and stakeholders at the port. Inaportnet is the leading solution for port services, where the acceleration of data exchange between stakeholders at the port can be done quickly, in order to minimize time and have an impact on speeding up ship services at the port. The performance of employees at the main Port Authority office is a concrete action in carrying out the work that has been given by government agencies. Every government agency always expects its employees to have work performance which will later provide optimal contributions to government agencies. In addition to providing an optimal contribution, it will improve the performance of government agencies. Broadly speaking, the continuity of a government agency is influenced by the performance of its employees. Employee performance has a very important role in running the organization. Employee performance is required to work seriously with their abilities to achieve good work results.